Xohán Casal through his Readings: the Literary Training of a Writer in the Postwar Period - Bermúdez Montes, Mª Teresa (Madrygal. Revista de Estudios Gallegos, 2023)
This paper presents an approach to the figure of the Galician writer Xohán Casal (1935-1960), using Casal’s personal writings to provide new keys for the analysis of his literary figure and narrative texts. During the 1950s, the young author made an effort to obtain a good reading training, despite the obstacles of censorship and the publishing shortage. The study of these unpublished materials –preserved as Fondo Xohán Casal in the Real Academia Galega– provides data and testimonies on the works that made up his collection of readings and also reveals Casal’s literary interests and relationships. The classic works by Eduardo Pondal, Manuel Curros Enríquez, Castelao and Luís Seoane were fundamental reference readings for Casal in the Galician field, while the pieces by Dickens, Brecht and O’Casey stand out among his preferences at the international level. The study of Casal’s writings provides useful references to locate this author both in relation to the Galician literary system and in relation to other systems.